2021
DOI: 10.3390/w13060789
|View full text |Cite
|
Sign up to set email alerts
|

Research on Descaling Characteristics and Simulation Calculation of a Coaxial High-Frequency Electronic Descaling Device

Abstract: High-frequency electronic descaling devices are physical water treatment methods that use a high-frequency electromagnetic field to prevent and remove scale. The effectiveness of the method is verified by monitoring the growth of scale on the surface of heat exchange tubes. The microstructure of scale obtained from experiments is analyzed by scanning electron microscope (SEM), and the action characteristics of high-frequency electromagnetic fields on water are explored by observing the change of solution conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Dissolving calcium carbonate on both sides of the pipe wall will increase the concentration of carbonate and bicarbonate in the solution, causing hydrolysis reaction with circulating water equation ( 8) and ( 9) , and the generated OHwill increase the PH of the solution. The increase of OHconcentration is shown by equation (13), and the equation moves to the right. Will continue to generate soft texture of calcium carbonate crystals, washed away by the water flow [15].…”
Section: Water Quality Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…Dissolving calcium carbonate on both sides of the pipe wall will increase the concentration of carbonate and bicarbonate in the solution, causing hydrolysis reaction with circulating water equation ( 8) and ( 9) , and the generated OHwill increase the PH of the solution. The increase of OHconcentration is shown by equation (13), and the equation moves to the right. Will continue to generate soft texture of calcium carbonate crystals, washed away by the water flow [15].…”
Section: Water Quality Parametersmentioning
confidence: 95%
“…In the case of resonance, the hydrogen bond of water molecules will break and form small groups of water molecules or even single water molecules, which will lead to dynamic equilibrium in aqueous solution.The research of Zhe Lv [12] showed that after the experimental solution was treated by electromagnetic, the hydrogen bond between water molecules was strengthened, more water molecular clusters were formed, and the hydration of ions in the solution was also strengthened, so that the water molecules were wrapped around Ca 2+ , resulting in no excessive crystallization of calcium carbonate. Yan [13] explored the effect of high frequency electromagnetic field on water by observing the change of the contact angle of the solution at different times. The experimental results show that the electromagnetic field reduces the contact angle of the solution, thus reducing the surface tension of the liquid and changing the physicochemical properties of the aqueous solution.…”
Section: Effects Of Electromagnetic Fields On the Performance Of Aque...mentioning
confidence: 99%
See 1 more Smart Citation
“…It requires a large amount of memory, and the convergence speed is also insufficient. Although the nonsequential simulation algorithm has been improved, its model establishment is relatively simple, the memory required for the operation is small, and the relative sequential convergence speed is relatively fast, but it still cannot meet the requirements in practical application [13,14].…”
Section: Reliability Evaluation Methods Of Relay Protectionmentioning
confidence: 99%
“…Therefore, adopting effective water treatment methods is crucial to ensure the normal operation and long-term stability of industrial circulating water systems. Researchers have proposed various methods to address these challenges, including physical cleaning, ultrasonic techniques, ion exchange resin methods [1], chemical agents, electrochemical approaches [2], and electromagnetic treatments [3][4][5]. Each method has its unique advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%